Planejamento estratégico de um residencial geriátrico - Nery, Samuel Corso (2021)
Due to constant market and technological changes, together with the need to obtain a competitive position, companies, regardless of their size or scope, should optimize their processes and make decisions, for this, strategic planning suits as an aid tool for these operations. This study aims to present the appropriate strategic planning of Residencial Geriátrico Solar Santa Tereza, a company that operates in the area of comprehensive care for the elderly and does not have any tool for managing the organizat ion. The research began by conducting interviews with the manager, employees and some customers, followed by the application of a questionnaire to most customers, which served as the basis for collecting data and developing the next steps. Therefore, it was possible to carry out an external analysis, identifying threats and opportunities, and an internal analysis, defining the company's strengths and weaknesses. In addition, the strategic posture of maintenance, that is recommended for the organization, was obtained, as well as establishing its objectives, goals and strategies, along with the development of its respective appropriate action plan, which can contribute to the company achieving a successful position in the active sector.